Myths and Realities of E-Learning: Exploratory Survey of Higher Education Students. (June 2014) - Morais, Eduardo; Morais, Carla; Paiva, João
The present study seeks to become a positive contribution to the research and development of e-learning systems by conducting an exploratory evaluation of the opinions of the academic community of the University of Porto about various technical and social dimensions present in the conception and deployment of learning management systems, both in the context of supporting face-to-face education and as technical infrastructure to blended and distance learning programmes. A survey by questionnaire was applied to 504 members of the academic community at the university, and it was found that among the participants there is still great scepticism towards e-learning and technologically mediated education, especially among younger students. Participants also considered that learning management systems presenting a plethora of features are not as desirable as systems focused on providing a pleasant and consistent user experience.